Dinoflagellate cyst production in the Cariaco Basin: A 12.5 year-long sediment trap study. (February 2019) - Bringué, Manuel; Pospelova, Vera; Tappa, Eric J.; Thunell, Robert C.
Highlights: We present the longest published sediment trap time series of dinoflagellate cyst production in the world. Seasonal variability is driven by the timing & strength of upwelling in the basin. Both autotrophic (∼11%) and heterotrophic (∼89%) dinoflagellates respond positively to upwelling. The strong 1997/98 El Niño event was followed by the lowest cyst fluxes of the record. The response of each dinoflagellate cyst taxon to environmental variability is detailed. Abstract: Seasonal and interannual variability in dinoflagellate cyst production were assessed using a 12.5 year-long sediment trap time series from the Cariaco Basin (southern Caribbean Sea). This study constitutes the longest such time series published to date, providing robust patterns of variability for individual dinoflagellate cyst taxa as well as for major phytoplanktonic and (micro-)zooplanktonic groups at the site. Cyst production is interpreted in the context of physico-chemical properties measured in situ at the mooring site (primarily reflecting seasonal upwelling), and considering potential interactions with other major components of the pelagic food web (e.g., diatoms, ciliates, copepods). The time series consists in >300 sediment trap samples, each representing ∼14 days of sedimentation, collected at the CARIACO station between Nov. 8, 1996 and May 19, 2009. Mass fluxes of biogenic silica, calcium carbonate and organic carbon reflect dominantly the timing and strength of wind-driven, seasonal upwelling that brings colder, nutrient-rich waters to the surface, fostering primary productivity and the export of biogenous materials to the depths. On seasonal time scales, dinoflagellate cyst production is closely coupled with upwelling strength, with higher cyst fluxes consistently observed under active upwelling conditions (average of 50.5 × 10 3 cysts m −2 day −1 ) compared to non-active upwelling intervals (29.0 × 10 3 cysts m −2 day −1 ). Year-to-year variability is characterized by a large increase in cyst production observed over the last ∼4 years of the time series (2006–2009) and minimum cyst fluxes recorded in the years 1998 and 1999, following the strong 1997/98 El Niño event. Dinoflagellate cyst assemblages are dominated by Brigantedinium spp. (59.1%), accompanied by Echinidinium delicatum (10.8%), Bitectatodinium spongium (8.4%), Spiny brown type A (2.9%) and Echinidinium spp. (2.4%). Cyst produced by both autotrophic and heterotrophic dinoflagellates generally respond positively to upwelling in the basin. Most cyst taxa are associated with active upwelling conditions (e.g., Bitectatodinium spongium, Brigantedinium spp., Echinidinium delicatum, Quinquecuspis concreta, Selenopemphix quanta, Spiny brown type C), with some showing higher fluxes under active but weak upwelling conditions (e.g., Echinidinium granulatum, Echinidinium spp., cyst of P. fukuyoi, Spiny brown type A). Other cyst taxa tend to show higher abundances at the onset of upwelling conditions (e.g., Echinidinium aculeatum, cyst of Protoperidinium stellatum ) or following active upwelling intervals (e.g., Lejeunecysta marieae, Selenopemphix nephroides ). The detailed response of each dinoflagellate cyst taxon to environmental variability is presented in the form of an atlas, providing photomicrographs and detailing overall monthly production, contribution to the total trap assemblage as well as cyst production over the 12.5 years of the time series.